A Glimpse Into the Microbiome of Sjögren’s Syndrome - Deng, Chuiwen; Xiao, Qiufeng; Fei, Yunyun (Frontiers in Immunology, 2022)
Sjögren’s syndrome (SS) is a common chronic systemic autoimmune disease and its main characteristic is lymphoid infiltration of the exocrine glands, particularly the salivary and lacrimal glands, leading to sicca symptoms of the mouth and eyes. Growing evidence has shown that SS is also characterized by microbial perturbations like other autoimmune diseases. Significant alterations in diversity, composition and function of the microbiota were observed in SS. The dysbiosis of microbiome correlates with worse symptoms and higher disease severity, suggesting that dysbiosis may be of great importance in the pathogenesis of SS. In this review, we provide a general view of recent studies describing the microbiota alterations of SS, the possible pathways that microbiota dysbiosis may trigger SS and the existence of the gut-ocular/gut-oral axis in SS.